Pendampingan Siswa melalui Bimbingan Islami untuk Pencegahan Perilaku Bullying di Sekolah - Suriyati Suriyati; Suriati Suriati; Muh. Anis; Makmur Jaya Nur; Riska Riska (INKAMKU : Integrasi Akademisi dan Masyarakat yang Berkualitas, 2025)
Bullying in schools is a worrying social phenomenon because it negatively impacts students' psychological, academic, and spiritual development. Bullying prevention efforts can be implemented not only through psychological and legal approaches, but also through religious approaches that instill Islamic moral values. This article describes the Student Creativity Program (PKM), which provides student mentoring through Islamic guidance as a preventive strategy against bullying behavior in schools. The method used is a participatory approach involving students, teachers, and school counselors. The mentoring focuses on instilling the values ​​of Islamic brotherhood, empathy, patience, and respect for others. The results of the activity indicate an increase in student awareness of the dangers of bullying and a growing sense of mutual respect and care among peers. Thus, Islamic guidance has proven effective as an alternative strategy for preventing bullying in schools because it integrates cognitive, affective, and spiritual aspects in developing student character. It is hoped that this program can be replicated in other schools as an effort to build a safe, peaceful, and noble educational environment